Surface chemical compositions and dispersity of starch nanocrystals formed by sulfuric and hydrochloric acid hydrolysis. - Benxi Wei; Xueming Xu; Zhengyu Jin; Yaoqi Tian (PLoS ONE)
Surface chemical compositions of starch nanocrystals (SNC) prepared using sulfuric acid (H2SO4) and hydrochloric acid (HCl) hydrolysis were analyzed by X-ray photoelectron spectroscopy (XPS) and FT-IR. The results showed that carboxyl groups and sulfate esters were presented in SNC after hydrolysis with H2SO4, while no sulfate esters were detected in SNC during HCl-hydrolysis. TEM results showed that, compared to H2SO4-hydrolyzed sample, a wider size distribution of SNC prepared by HCl-hydrolysis were observed. Zeta-potentials were -23.1 and -5.02 mV for H2SO4- and HCl-hydrolyzed SNC suspensions at pH 6.5, respectively. Nevertheless, the zeta-potential values decreased to -32.3 and -10.2 mV as the dispersion pH was adjusted to 10.6. After placed 48 h at pH 10.6, zeta-potential increased to -24.1 mV for H2SO4-hydrolyzed SNC, while no change was detected for HCl-hydrolyzed one. The higher zeta-potential and relative small particle distribution of SNC caused more stable suspensions compared to HCl-hydrolyzed sample.